AIR MATH

Math Question

Kate begins solving the equation \( \frac{2}{3}(6 x-3)=\frac{1}{2}(6 x-4) \). When she adds 2 to both sides, the equation \( 4 x=3 x \) Her work is correct and is shown below. results. Which solution will best illustrate what happens to \( \times \) ?
\[
\frac{2}{3}(6 x-3)=\frac{1}{2}(6 x-4)
\]
The equation has infinite solutions.
\( 4 x-2=3 x-2 \)
The equation has one solution: \( x=0 \).
The equation has one solution: \( x=\frac{4}{3} \).
The equation has no solution.

Solution

solution

AIR MATH homework app,
absolutely FOR FREE!

  • AI solution in just 3 seconds!
  • Free live tutor Q&As, 24/7
  • Word problems are also welcome!
appstoreplaystore

Scan the QR code below
to download AIR MATH!

qrcode